A Study of the Source Traffic Generator Using Poisson Distribution for ABR Service. (31st July 2012) - Hosamo, Mohsen
Abstract : This paper describes modeling of the available bit rate (ABR) source traffic in asynchronous transfer mode (ATM) network usingB L P o s / G T E X P traffic generator, which employs Poisson distribution for modeling the burst length (B L P o s ) and exponential distribution for modeling the gap time (G T E X P ). This traffic generator inherits the advantages of both Poisson and exponential distribution functions to achieve enhanced link performance. Analytical and simulation results forB L P o s / G T E X P traffic generator have been presented and compared.